Water education: A valuable tool for water sustainability - Elizabeth Vgenopoulou; Cavoura, Olga; Papadas, Ioannis; Damikouka, Ioanna (International Journal of Occupational Safety and Health, 2026)
Introduction: Water is a fundamental natural resource for health, social well-being and sustainable development. Despite the implementation of technical and institutional measures, water challenges persist, highlighting the need for interventions that also focus on human behavior. In this context, education is recognized as a critical factor in shaping sustainability-oriented approaches to water management. The aim of this study is to review and synthesize the literature on water education, with emphasis on educational levels, thematic units, pedagogical approaches and reported learning outcomes. Methods: A narrative literature review was conducted in international scientific databases. Studies were selected that concerned educational initiatives and interventions on water within the context of Environmental Education and Education for Sustainable Development. Results: The findings show that most interventions are implemented in primary and secondary education and utilize experiential and participatory pedagogical approaches. Most studies document positive effects on knowledge and attitudes, while data on long-term behavioral change remain limited. Conclusion: Water education contributes substantially to strengthening water culture and environmental awareness, while highlighting the need for more systematic evaluation and further research on long-term educational outcomes.